1984
DOI: 10.1007/bf00139998
|View full text |Cite
|
Sign up to set email alerts
|

The effect of yeast extract on the fermentation of glucose to 2,3-butanediol by Bacillus polymyxa

Abstract: The fermentation of glucose to 2,3-butanediol by Bacillus polymyxa was improved by increasing the amount of yeast extract in the culture medium. A level of 1.5% (w/v) resulted in optimal 2,3-butanediol production.A comparable fermentation could be achieved with 0.5% yeast extract if the phosphate level of the medium was increased from 0.0026 to 0.078 M and the medium was supplemented with 40 ~M iron and 1.7 ~M manganese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 12 publications
0
4
2
Order By: Relevance
“…Furthermore, in our experiment, Fe 2+ and Mn 2+ played only minor roles in the fermentation, which is different from the report of Laube et al. . They reported that single or combined addition of Fe 2+ and Mn 2+ would show higher yields of 2,3‐BD.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in our experiment, Fe 2+ and Mn 2+ played only minor roles in the fermentation, which is different from the report of Laube et al. . They reported that single or combined addition of Fe 2+ and Mn 2+ would show higher yields of 2,3‐BD.…”
Section: Resultscontrasting
confidence: 99%
“…Of these factors, urea was used to replace the yeast extract powder, peptone, or any other costly nitrogen source in the production of 2,3-BD. Furthermore, in our experiment, Fe 2+ and Mn 2+ played only minor roles in the fermentation, which is different from the report of Laube et al [26]. They reported that single or combined addition of Fe 2+ and Mn 2+ would show higher yields of 2,3-BD.…”
Section: Variable Levelscontrasting
confidence: 99%
“…However, optimum production was observed with 1.5 : < YE in the same fermentation system when the glucose concentration was increased to 5 %. 47 Yu & Saddler4' also observed increased yield of 2,3-butanediol with 1 : < YE in the fermentation of Klebsiellu pneumoniae. Like yeast extract, pH seems to influence 2,3-butanediol production.'…”
Section: 54mentioning
confidence: 93%
“…15 In addition, for the nitrogen sources in 2,3-BDO fermentation, most of the previous works have used yeast extract or ammonium salts. 16,17 Because of their relatively high cost, the use of these nitrogen sources for the industrial production of 2,3-BDO may not be feasible. 18 Condensed distillers solubles (CDS) are a byproduct of BE production that is extensively used as a component of the medium for the culture of microorganisms in industrial fermentation.…”
Section: Introductionmentioning
confidence: 99%